DO COMPREHENSIVE INCOME AND ATTRIBUTED INCOME PERFORMANCE AFFECT THE COMPANY'S CAPITAL STRUCTURE POLICY? - Miladiah Kusumaningarti; Marhaendra Kusuma (Journal of Applied Finance and Accounting, 2026)
Since the use of the theoretical basis of fair value accounting and entity theory in Financial Accounting Standards, the meaning of profit has expanded, until finally the comprehensive income and attributable income items appeared in the presentation of the income statement. Unfortunately, in measuring profitability and its relationship to capital structure policy, comprehensive income and attributable income have not been widely used. The purpose of this study is to prove the effect of comprehensive income and attributable income on capital structure policy. Data of 9,660 firms-years from 2,415 financial reports of companies listed on the Indonesia Stock Exchange (IDX), Malaysia (BM), Thailand (SET), Singapore (SGX), Philippines (PSE), and Vietnam (HOSE) during the observation period of 2020 - 2023. The results of the study indicate that the achievement of comprehensive profit and attributable profit performance has a negative effect on the company's capital structure policy. In line with the pecking order theory, companies will use internal funding from profit achievements, including comprehensive profit and attributable profit, before finally using external funding sources from debt and share issuance. The originality of this study is the examination of the effect of comprehensive profit and attributable profit on capital structure.